Effects of Expanded Polytetrafluoroethylene Porous Membrane Covering and Biochar on Nitrogen, Phosphorus, and Potassium Contents in Aerobic Composting - Jie Cao; Ruirong Li; Haoli Qu; Pengjun Wang; Jingjing Fu; Yan Gong; Mingjiang Chen (BioResources, 2024)
The effects of covering technology and the combined membrane covering with biochar on nutritional elements content during the aerobic composting process of agricultural waste were studied. The results showed that the concentration effect of organic matter degradation during composting increased the nitrogen, phosphorus, and potassium contents in all treatment groups. The proportion of available phosphorus and available potassium also increased to varying degrees. Compared with composting without an expanded poly(tetrafluoroethylene) (PTFE) covering with 0.2 to 0.4 µm pores, the covered composting increased the total nitrogen, total phosphorus, total potassium, available phosphorus, and available potassium contents by 13.1%, 12.6%, 7.4%, 21.5%, and 16.6%, respectively, while the addition of biochar to polymer membrane-covered composting increased the total nitrogen, total phosphorus, total potassium, available phosphorus, and available potassium contents by 19.7%, 13.7%, 8.3%, 18.0%, and 20.2%, respectively. This study indicated that membrane covering technology can effectively increase the nutrient element contents in compost products and the availability of phosphorus and potassium and that the addition of biochar enhances these effects.